A study of fake news reading and annotating in social media context. Issue 1 (3rd April 2021) - Simko, Jakub; Racsko, Patrik; Tomlein, Matus; Hanakova, Martina; Moro, Robert; Bielikova, Maria
ABSTRACT: The online spreading of fake news is a major issue threatening entire societies. Much of this spreading is enabled by new media formats, namely social networks and online media sites. Researchers and practitioners have been trying to answer this by characterising the fake news and devising automated methods for detecting them. The detection methods had so far only limited success, mostly due to the complexity of the news content and context and lack of properly annotated datasets. One possible way to boost the efficiency of automated misinformation detection methods is to imitate the detection work of humans. It is also important to understand the news consumption behaviour of online users. In this paper, we present an eye-tracking study, in which we let 44 lay participants to casually read through a social media feed containing posts with news articles, some of which were fake. In a second run, we asked the participants to decide on the truthfulness of these articles. We also describe a follow-up qualitative study with a similar scenario but this time with seven expert fake news annotators. We present the description of both studies, characteristics of the resulting dataset (which we hereby publish) and several findings.